2012
DOI: 10.1016/j.brainres.2012.02.013
|View full text |Cite
|
Sign up to set email alerts
|

Taste neophobia and c-Fos expression in the rat brain

Abstract: Taste neophobia refers to a reduction in consumption of a novel taste relative to when it is familiar. To gain more understanding of the neural basis of this phenomenon, the current study examined whether a novel taste (0.5% saccharin) supports a different pattern of c-Fos expression than the same taste when it is familiar. Results revealed that the taste of the novel saccharin solution evoked more Fos immunoreactivity than the familiar taste of saccharin in the basolateral region of the amygdala, central nucl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
52
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 54 publications
(60 citation statements)
references
References 48 publications
7
52
0
1
Order By: Relevance
“…The present results not only reverse this oversight but they also bring other evidence into sharper focus with regard to an involvement of the GT in taste neophobia. That it, using analysis of c-Fos activation, Lin, Roman, Arthurs, and Reilly [31] recently found that in addition to the GC, basolateral amygdala (BLA), and central nucleus of the amygdala, the GT was also activated by exposure to a novel, but not a familiar, taste stimulus. Furthermore, in a voluntary intake task involving 15-min trials, Lin et al [27] reported that palatability (assessed with lick cluster size) was significantly lower when the tastant was novel relative to when the same stimulus was familiar as a consequence of repeated exposures.…”
Section: Discussionmentioning
confidence: 99%
“…The present results not only reverse this oversight but they also bring other evidence into sharper focus with regard to an involvement of the GT in taste neophobia. That it, using analysis of c-Fos activation, Lin, Roman, Arthurs, and Reilly [31] recently found that in addition to the GC, basolateral amygdala (BLA), and central nucleus of the amygdala, the GT was also activated by exposure to a novel, but not a familiar, taste stimulus. Furthermore, in a voluntary intake task involving 15-min trials, Lin et al [27] reported that palatability (assessed with lick cluster size) was significantly lower when the tastant was novel relative to when the same stimulus was familiar as a consequence of repeated exposures.…”
Section: Discussionmentioning
confidence: 99%
“…First, the literature shows that MeA lesions have little or no influence on CTA acquisition [1,46,62,66,74]. Second, unlike the BLA and GC, c-Fos expression is not elevated in the MeA consequent to intake of a novel tastant (0.5% saccharin [39]). Stated in this way, one may doubt whether the MeA has a role in taste neophobia per se.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, a total of three experiments were conducted involving asymmetric unilateral lesions of the BLA and GC (Experiment 1), the GC and MeA (Experiment 2), and the MeA and BLA (Experiment 3). To maintain comparability with our previous research, the experiments in the present study employed the same taste neophobia procedure used in Lin et al ([40]; also see [37,39]) that involved repeated exposures to a 0.5% saccharin solution in water deprived rats.…”
Section: Introductionmentioning
confidence: 85%
“…Using our standard procedure (e.g., Lin, Roman, Arthurs & Reilly, 2012; Lin, Roman, St. Andre & Reilly, 2009), Lin, Amodeo, Arthurs and Reilly (2012) examined the neophobic reactions of separate groups of water-deprived rats to three tastants: saccharin, quinine and Polycose. Saccharin and quinine were chosen because they each show a pronounced neophobic reaction in terms of volume consumed; Polycose was included to extend the generality of the work of Barot and Bernstein (2005) that this tastant does not support a neophobic response.…”
Section: Lick Pattern Analysis and Palatabilitymentioning
confidence: 99%